IMPLEMENTATION OF LOCAL WISDOM-BASED SCHOOL MANAGEMENT THROUGH ECO-ENZYME PROJECT RESEARCH TO ENHANCE ENVIRONMENTAL AWARENESS (Lex localis - Journal of Local Self-Government, 2025)
Schools play a critical role in shaping students’ environmental awareness, especially when management practices are rooted in local wisdom that emphasizes harmony with nature. Eco-enzyme projects provide a concrete avenue for integrating environmental education into school management. This study aims to evaluate the implementation of school management based on local wisdom through an eco-enzyme project research approach in enhancing environmental awareness among students at a State Islamic Senior High School in East Jakarta. The research employed the CIPP evaluation model Context, Input, Process, and Product to comprehensively assess needs, resources, implementation, and outcomes. Data were collected from grade XI students, teachers, and school administrators using observations, interviews, documentation, and questionnaires. The data were analyzed through reduction, display, and conclusion drawing. The findings show that (1) in the context aspect, the program was relevant to the school’s vision and local wisdom values emphasizing harmony with the environment; (2) in the input aspect, there was support from teachers, basic laboratory facilities, and school funding (3) in the process aspect, the implementation of the eco-enzyme project was effective with active student participation (4) in the product aspect, the activities significantly increased students’ environmental awareness and produced eco-enzyme products that can be utilized as liquid organic fertilizer. Therefore, the eco-enzyme project research based on local wisdom has proven effective in strengthening school management oriented toward sustainable education and environmental care. The integration of local wisdom-based eco-enzyme project research into school management contributes meaningfully to fostering sustainable education practices and enhancing students’ environmental responsibility.